Influence of social media followers on revenues: a pilot study of Europe's top 20 football clubs - Valcarce Torrente, Manel; Pérez González, Benito; Guevara Pérez, Juan Carlos; López Carril, Samuel (Academia Revista Latinoamericana de Administración, 2025)
Purpose In an increasingly digitised sport ecosystem, social media has emerged as a primary tool for sport managers to engage with industry stakeholders. This pilot study aims to investigate whether there is a correlation between the number of followers on football teams' social media accounts and the annual revenue they generate. Design/methodology/approach We sampled the number of followers on Facebook, Twitter, Instagram and TikTok of the top 20 European football clubs based on their annual revenue. Employing a balanced panel data approach for the four years (2020¿2023), our analysis comprises a total of 80 observations in a regression model. Findings The study¿s findings indicate a correlation between the number of social media followers and annual revenue, with particularly strong correlations observed for Facebook and TikTok. Additionally, significant growth in the number of followers on Instagram and TikTok was identified during the study period. Research limitations/implications The study¿s limitations suggest opportunities for future research. Exploring the bidirectional SP¿FP relationship could reveal how financial sustainability impacts fans¿ social media behaviour. Further studies might analyse specific leagues, other sports or platforms like YouTube and WhatsApp or apply longitudinal data to a single platform. Additionally, qualitative or mixed methods, such as interviews or focus groups with stakeholders, could enrich understanding of social media¿s subjective aspects. This pilot study does not claim definitive conclusions but aims to inspire further research in the dynamic realm of social media and digital technologies, broadening knowledge in this rapidly evolving field. Originality/value The findings have implications for sport managers in designing and optimising social media management strategies, given their potential impact on revenue generation. The study contributes to a better understanding of the revenue-generating potential of social media in the football industry. Furthermore, this is one of the first studies to simultaneously analyse the use of Facebook, Twitter, Instagram and TikTok by football clubs over four years.